Composite anodic oxidation film and preparation method and application thereof
Patent Information
- Application Number
- CN202611115341.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-09-18
AI Technical Summary
针对现有技术中的阳极氧化膜无法同时实现高耐腐蚀性、高耐电压绝缘性,高阻抗性的技术问题,本申请提供了一种复合阳极氧化膜的制备方法,同时,本申请提供了一种复合阳极氧化膜,进一步地,本申请还提供了一种复合阳极氧化膜的应用
(1)本发明的一种复合阳极氧化膜的制备方法,包括以下步骤:对金属基材进行前处理;采用酸性电解液对所述金属基材进行第一次阳极氧化,以形成多孔氧化层;在所述多孔氧化层形成后,采用包含己二酸铵的中性电解液进行第二次阳极氧化,以在所述金属基材与所述多孔氧化层之间形成致密壁垒氧化层,得到由位于内侧的壁垒氧化层和位于外侧的多孔氧化层组成的复合阳极氧化膜。整体工艺分为一次阳极氧化多孔氧化层成型、二次阳极氧化壁垒氧化层增厚两个核心阶段,其中,一次阳极氧化,在基材表面生成厚度均匀、结合力优异的多孔氧化层,该层作为复合膜的上部功能层,具备良好的结构适配性与基础防护性能,为后续二次壁垒层生长提供稳定基底;二次阳极氧化依托高频高压、中性电解液己二酸铵的工艺特性,在一次多孔膜与基材的界面处,生长成无气孔、高致密的壁垒型氧化膜,通过两次差异化阳极氧化复合成型,构建“底层致密壁垒层+上部多孔防护层”的双层复合膜结构,同步提升氧化膜的耐腐蚀性、耐电压绝缘性能和阻抗,实现两种工艺优势互补,弥补单一工艺的性能短板,适配高端精密金属零部件的严苛使用工况。克服现有常规草酸/混酸多孔氧化工艺耐蚀性不足、单一壁垒型氧化工艺耐电压绝缘性薄弱的技术缺陷。
Smart Images

Figure CN122773451A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum alloy surface treatment technology, specifically relating to a composite anodic oxide film, its preparation method, and its application. Background Technology
[0002] Conventional oxalic acid oxidation and mixed acid oxidation processes are industry-standard porous anodizing processes that rely on an acidic electrolyte system to grow the film. Due to the limitations of the acidic electrolyte, the oxide film structure produced by this process is primarily porous, with an extremely thin bottom barrier layer, only about 50 nm thick. This thin barrier layer cannot form an effective protective barrier structure, resulting in poor overall oxide film density and barrier properties. In humid and corrosive environments, it is highly susceptible to problems such as media penetration, film damage, and substrate corrosion, exhibiting significant shortcomings in corrosion resistance and failing to meet the requirements of highly corrosive operating conditions.
[0003] Single-barrier anodizing processes can generate dense, non-porous barrier oxide films, effectively solving the problem of insufficient corrosion resistance in porous films. However, this process is limited by the output characteristics of conventional DC power supplies, resulting in a very low upper limit for film growth, with the maximum film thickness reaching only 300 nm. Insufficient film thickness directly leads to weak breakdown voltage and insulation properties of the oxide film, making it prone to leakage and breakdown failure under high-voltage conditions. Furthermore, its voltage resistance and insulation cannot meet the standards for use in high-end precision equipment.
[0004] In summary, both existing single porous oxidation processes and single barrier oxidation processes have performance shortcomings and cannot simultaneously achieve high corrosion resistance, high voltage resistance insulation, and high impedance. The industry lacks an anodizing solution that can take into account multiple performance characteristics, structural stability, and process control, which restricts the development and application of surface protection technology for high-requirement metal parts.
[0005] Therefore, there is an urgent need for a method for preparing anodic oxide films that can simultaneously achieve high corrosion resistance, high voltage resistance and insulation, and high impedance. Summary of the Invention
[0006] 1. The problem to be solved To address the technical problem that existing anodic oxide films cannot simultaneously achieve high corrosion resistance, high voltage resistance, and high impedance, this application provides a method for preparing a composite anodic oxide film, as well as a composite anodic oxide film itself, and further, an application of the composite anodic oxide film.
[0007] 2. Technical Solution To achieve the above objectives, the provided technical solution is as follows: The first aspect of this invention provides a method for preparing a composite anodic oxide film, comprising the following steps: Pretreatment of the metal substrate; The metal substrate is subjected to a first anodic oxidation using an acidic electrolyte to form a porous oxide layer; After the porous oxide layer is formed, a second anodic oxidation is performed using a neutral electrolyte containing ammonium adipate to form a dense barrier oxide layer between the metal substrate and the porous oxide layer, resulting in a composite anodic oxide film consisting of an inner barrier oxide layer and an outer porous oxide layer.
[0008] Furthermore, the thickness of the porous oxide layer formed by the first anodizing is 1 μm to 100 μm.
[0009] The voltage withstand capability of the oxide film is closely related to the thickness of the porous oxide layer and the thickness of the composite oxide film. As the thickness increases, the voltage withstand capability improves, making it suitable for high-voltage insulation protection in different scenarios.
[0010] Preferably, the thickness of the porous oxide layer formed by the first anodizing can be any value within any of the following ranges: 1 μm ~ 90 μm, 1 μm ~ 80 μm, 1 μm ~ 70 μm, 1 μm ~ 60 μm, 1 μm ~ 50 μm, 1 μm ~ 40 μm, 1 μm ~ 30 μm, 1 μm ~ 20 μm, 1 μm ~ 10 μm.
[0011] Furthermore, the barrier oxide layer formed by the second anodizing has a thickness of 150 nm to 400 nm.
[0012] A barrier oxide layer is formed between the porous oxide layer and the metal substrate, and the thickness of the barrier oxide layer is 150 nm to 400 nm. The structure of this composite oxide film has higher voltage resistance than that of a single porous oxide layer. At the same time, it has stronger corrosion resistance and higher impedance than that of a single barrier oxide layer.
[0013] Preferably, the thickness of the barrier oxide layer formed by the second anodizing can be any value within any of the following ranges: 150 nm to 350 nm, 200 nm to 350 nm, 250 nm to 350 nm, or 300 nm to 350 nm.
[0014] Furthermore, the current density for the first anodizing is 0.5 A / dm³. 2 ~2 A / dm 2 The voltage for the second anodizing is 100 V to 500 V. The temperature for the first anodizing is 0 ℃ to 50 ℃; the temperature for the second anodizing is 15 ℃ to 50 ℃.
[0015] The first anodizing time is 30 min to 200 min; the second anodizing time is 30 min to 60 min.
[0016] Within this current density range, a porous layer structure with uniform pore size and orderly arrangement can be stably formed, providing a stable substrate for secondary oxidation.
[0017] Within this voltage range, a thicker and denser secondary anodic oxide film structure, namely a barrier layer film structure, can be formed, which improves the pressure resistance of the composite anodic oxide film and simultaneously enhances its corrosion resistance and impedance.
[0018] When the temperature and time of the first anodizing are controlled within this range, a porous oxide layer with uniform thickness and excellent adhesion can be generated; when the temperature and time of the second anodizing are controlled within this range, a barrier oxide layer with no pores and high density can be grown.
[0019] Preferably, the temperature of the first anodizing is 15 ℃ to 30 ℃; the temperature of the second anodizing is 30 ℃ to 50 ℃.
[0020] Preferably, the voltage for the second anodizing is 100 V to 200 V.
[0021] Furthermore, the acidic electrolyte includes one or both of oxalic acid and sulfuric acid.
[0022] Furthermore, the oxalic acid has a mass concentration of 1% to 20%; the ammonium adipate has a mass concentration of 1% to 20%.
[0023] The first anodizing process, with oxalic acid concentration within this range, can generate a porous oxide layer with uniform thickness and excellent adhesion on the substrate surface. The second anodizing process uses ammonium adipate as a neutral electrolyte. Unlike strongly acidic electrolytes, neutral electrolytes have very weak or no chemical dissolution effect on the already formed oxide film, thus enabling the growth of a thicker functional film layer more effectively. This concentration range allows the film layer to continue growing in a relatively stable and controllable environment, resulting in a thicker and denser barrier layer.
[0024] Preferably, the oxalic acid has a mass concentration of 1% to 10%; and the ammonium adipate has a mass concentration of 1% to 10%.
[0025] Furthermore, the pretreatment includes degreasing, water washing, etching, water washing, purification, and high-pressure water washing.
[0026] A second aspect of the present invention provides a composite anodic oxide film, characterized in that it comprises a porous oxide layer located on the surface of a metal substrate; A dense barrier oxide layer located between the metal substrate and the porous oxide layer; The thickness of the barrier oxide layer is 150 nm to 400 nm.
[0027] Furthermore, the thickness of the porous oxide layer is 1 μm to 100 μm.
[0028] The third aspect of the present invention relates to an application of a composite anodic oxide film, wherein the composite anodic oxide film described in the second aspect of the present invention, or the composite anodic oxide film obtained by the preparation method described in the first aspect of the present invention, is applied to the preparation of high-end precision metal materials.
[0029] 3. Beneficial effects Compared with existing known technologies, the technical solution provided by this invention has the following beneficial effects: (1) A method for preparing a composite anodic oxide film according to the present invention includes the following steps: pretreatment of a metal substrate; first anodic oxidation of the metal substrate using an acidic electrolyte to form a porous oxide layer; and second anodic oxidation using a neutral electrolyte containing ammonium adipate after the porous oxide layer is formed to form a dense barrier oxide layer between the metal substrate and the porous oxide layer, thereby obtaining a composite anodic oxide film composed of a barrier oxide layer located on the inner side and a porous oxide layer located on the outer side. The overall process is divided into two core stages: primary anodizing to form a porous oxide layer and secondary anodizing to thicken a barrier oxide layer. Primary anodizing generates a porous oxide layer with uniform thickness and excellent adhesion on the substrate surface. This layer, serving as the upper functional layer of the composite membrane, possesses good structural adaptability and basic protective performance, providing a stable substrate for the subsequent growth of the secondary barrier layer. Secondary anodizing, leveraging the characteristics of high-frequency, high-voltage, and neutral ammonium adipate electrolyte, grows a non-porous, highly dense barrier oxide film at the interface between the primary porous membrane and the substrate. Through these two differentiated anodizing composite formations, a two-layer composite membrane structure of "a dense barrier layer at the bottom + a porous protective layer at the top" is constructed. This simultaneously improves the oxide film's corrosion resistance, voltage resistance, insulation performance, and impedance, achieving complementary advantages between the two processes and compensating for the performance shortcomings of a single process. This makes it suitable for the demanding operating conditions of high-end precision metal components. It overcomes the technical deficiencies of existing conventional oxalic acid / mixed acid porous oxidation processes (insufficient corrosion resistance) and single barrier oxidation processes (weak voltage resistance and insulation).
[0030] (2) A composite anodic oxide film of the present invention includes a porous oxide layer located on the surface of a metal substrate; a dense barrier oxide layer located between the metal substrate and the porous oxide layer; the thickness of the barrier oxide layer is 150 nm to 400 nm. The composite anodic oxide film of the present invention has a double-layer composite structure, which can be clearly distinguished by SEM film cross-section observation: the bottom layer is a dense non-porous barrier layer with a thickness of 150 nm to 400 nm, and the upper layer is a porous oxide layer. The two film layers are tightly bonded, without delamination or pore defects, forming a composite anodic oxide film with complementary structure, which simultaneously improves the corrosion resistance, voltage resistance, insulation performance and impedance of the oxide film. The composite anodic oxide film of Example 1 has a voltage resistance of 1078 V, which is 25.93% higher than that of Comparative Example 1; the impedance is 3320 Ω, which is 14.48% higher than that of Comparative Example 2; the composite anodic oxide film of Example 1 has a corrosion resistance time of 34 min in 3% HCl, which is 78.95% higher than that of Comparative Example 2.
[0031] (3) An application of the composite anodic oxide film of the present invention is to apply the composite anodic oxide film to the preparation of high-end precision metal materials. For extremely thin composite anodic oxide films, they are mainly used for precision parts with extremely high dimensional accuracy requirements and insulation or corrosion resistance requirements, such as precision sensor housings in medical devices, precision positioning and conduction components in semiconductor equipment, dials and bases of high-end instruments and meters, and precision electronic structural parts that require conductive / insulating isolation. For thicker composite anodic oxide films, they are used for parts that are subjected to sliding friction, high voltage stress or moderate chemical corrosion, such as in the fields of aerospace, automobiles and heavy equipment. Attached Figure Description
[0032] Figure 1 The image shows the surface morphology of the composite anodic oxide film prepared in Example 1 under low magnification using SEM. Figure 2 The surface morphology of the composite anodic oxide film prepared in Example 1 is shown by SEM at high magnification. Figure 3 SEM image of the composite anodic oxide film prepared in Example 2; Figure 4 SEM image of the composite anodic oxide film prepared in Example 3; Figure 5 SEM image of the anodic oxide film prepared in Comparative Example 1; Figure 6 Here is a SEM image of the surface morphology of the anodic oxide film prepared in Comparative Example 2; where, Figure 6 In the image, 'a' represents a low-magnification morphology diagram. Figure 6 In the image, b represents the morphology at high magnification. Figure 7Here is a SEM image of the surface morphology of the composite anodic oxide film prepared in Example 4; wherein, Figure 7 In the image, 'a' represents a low-magnification morphology diagram. Figure 7 In the image, b represents the morphology at high magnification. Figure 8 A bar chart showing the impedance values of different oxide films prepared in Comparative Example 4; Figure 9 This is the anode tank for the anodizing process of this application; Figure 10 It is an insulation withstand voltage tester; Figure 11 For insulation resistance testing; Figure 12 This is a diagram showing the corrosion resistance test results. Figure 13 The process flow diagram for preparing the composite anodic oxide film in this embodiment is shown. Figure 14 The process flow diagrams are for the preparation of anodic oxide films in comparative examples 1 to 4. Detailed Implementation
[0033] To further understand the content of this invention, the invention will be described in detail with reference to the embodiments.
[0034] The present application will be further described below with reference to specific embodiments.
[0035] It should be noted that terms such as "upper", "lower", "left", "right", and "middle" used in this specification are only for clarity of description and are not intended to limit the scope of implementation. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered as within the scope of this application.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the term “and / or” as used herein includes any and all combinations of one or more of the associated listed items.
[0037] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0038] As used herein, the term “about” is used to provide for the flexibility and imprecision associated with a given term, measure, or value. Those skilled in the art can readily determine the degree of flexibility for a particular variable. As used herein, the term "at least one of..." is intended to be synonymous with "one or more of...". For example, "at least one of A, B, and C" explicitly includes only A, only B, only C, and combinations thereof. Concentration, amount, and other numerical data may be presented herein in range format. It should be understood that such range format is used only for convenience and brevity and should be flexibly interpreted to include not only the numerical values explicitly stated as the limits of the range, but also all individual numerical values or subranges covered within the range, as if each numerical value and subrange were explicitly stated. For example, a numerical range of about 1 to about 4.5 should be interpreted to include not only the explicitly stated limits of 1 to about 4.5, but also individual numbers (such as 2, 3, 4) and subranges (such as 1 to 3, 2 to 4, etc.). The same principle applies to ranges that describe only one numerical value, such as "less than about 4.5," which should be interpreted to include all the values and ranges described above. Furthermore, this interpretation should apply regardless of the breadth of the range or characteristic described.
[0039] Example 1 The method for preparing the composite anodic oxide film in this embodiment includes the following steps: S1. Pretreatment: The metal substrate sample is 6061 aluminum alloy, and it is subjected to degreasing, water washing, etching, water washing, purification and high-pressure water washing in sequence. S2. First anodizing treatment: The pretreated sample is placed in an electrolyte for the first anodizing. The electrolyte for the first anodizing is a 5% (w / w) oxalic acid solution. The anode temperature is controlled at 20 °C, and a constant current mode is used with a current density of 1 A / dm³. 2 The anode time is determined according to the required film thickness. The anode time is 100 min, which forms a porous oxide layer with a thickness of 20 μm. Using oxalic acid electrolyte and a controllable DC power supply, a porous oxide layer with uniform thickness and excellent adhesion is generated on the substrate surface. This layer serves as the upper functional layer of the composite membrane, possessing good structural adaptability and basic protective performance, and providing a stable substrate for the subsequent growth of the secondary barrier layer.
[0040] S3. Second anodizing treatment (barrier anodizing): The sample obtained from the first anodizing treatment is washed with water, dried, and subjected to a second anodizing. The electrolyte for the second anodizing is a 5% (w / w) ammonium adipate neutral solution. The anode temperature is controlled at 40 ℃, the voltage is 200 V using a voltage stabilization method, and the anodizing time is 45 min to form a dense barrier oxide layer. The sample is then washed with water and dried at 60 ℃ for 2 h to obtain a composite anodized film consisting of a barrier oxide layer on the inner side and a porous oxide layer on the outer side. This anodized film has a double-layer composite structure.
[0041] Anodizing is carried out in an anode tank, such as... Figure 9 As shown.
[0042] Relying on the process characteristics of high frequency, high voltage, and neutral electrolyte, a non-porous, highly dense barrier oxide film is generated at the interface between the porous oxide layer and the substrate. The thickness of the barrier oxide layer ranges from 275.4 nm to 322.8 nm, with an average thickness of 293 nm.
[0043] Voltage withstand test, impedance test and corrosion resistance test were performed on the anodic oxide film specimen containing the double-layer composite structure. The results are shown in Table 1: I. Withstand Voltage Test Method: A Chroma insulation withstand voltage tester (model 19073) was used. Figure 10 As shown, the withstand voltage performance of the oxide film was measured. The upper limit of the breakdown voltage was 5 kV, the voltage rise time was 200 s, the holding time was 10 s, and the leakage current was set to 1 mA. The instantaneous voltage at which the oxide film breaks down during the voltage rise process represents the insulation withstand voltage value of the oxide film.
[0044] II. Impedance Testing Method: An insulation resistance tester (model TH2826) from Tonghui was used. Figure 11 As shown, the mode is set to impedance measurement. A glass test tube is fixed on the surface of the test piece, and a 3.5% sodium chloride solution is injected into the test tube. One end of the instrument is in contact with the bare aluminum part of the test piece, and the other end is in contact with the sodium chloride solution. The impedance value of the test piece is then measured.
[0045] III. Corrosion Resistance Test Method: Fix the sample surface to a glass test tube, pour a 3% hydrochloric acid solution or a 5% HF solution into the test tube, and record the time it takes for bubbles to form in the solution. This is used to characterize the corrosion resistance of the oxide film. Figure 12 As shown.
[0046] The preparation process flow of this embodiment is as follows: Figure 13 As shown, the final oxide film has a double-layer composite structure, which can be clearly distinguished by SEM cross-sectional observation of the film layers, such as... Figure 1 and Figure 2 As shown, the bottom layer is a dense, non-porous barrier layer with an average thickness of 293 nm, and the top layer is a porous oxide layer with a thickness of 20 μm. The two layers are tightly bonded, without delamination or pore defects, forming a composite anodic oxide film with complementary structures. Figure 1 and Figure 2 The film thickness values marked in the text are the film thicknesses for the corresponding locations.
[0047] The film thickness of the cross section was measured by SEM: the obtained anode sample was cut, mounted, polished and then observed by SEM cross section.
[0048] Example 2 The method for preparing the composite anodic oxide film in this embodiment includes the following steps: S1. Pretreatment: The metal substrate sample is 6061 aluminum alloy, and it is subjected to degreasing, water washing, etching, water washing, purification and high-pressure water washing in sequence. S2. First anodizing treatment: The pretreated sample is placed in an electrolyte for the first anodizing. The electrolyte for the first anodizing is a 5% (w / w) oxalic acid solution. The anode temperature is controlled at 20 °C, and a constant current mode is used with a current density of 1 A / dm³. 2 The anode time is determined according to the required film thickness. The anode time is 100 min, which forms a porous oxide layer with a thickness of 20 μm. S3. Second anodizing treatment: The sample obtained from the first anodizing treatment is washed with water, dried, and subjected to a second anodizing. The electrolyte for the second anodizing is a 5% (w / w) ammonium adipate neutral solution. The anode temperature is controlled at 40 ℃, and a voltage of 150 V is used in a stabilizing mode. The anodizing time is 45 min, forming a dense barrier oxide layer. The sample is then washed with water and dried at 60 ℃ for 2 h, resulting in a composite anodized film consisting of a barrier oxide layer on the inner side and a porous oxide layer on the outer side. This anodized film has a double-layer composite structure.
[0049] The final oxide film formed in this embodiment is a two-layer composite structure. The bottom layer is a dense, non-porous barrier oxide layer, and the top layer is a porous oxide layer. The two layers are tightly bonded, without delamination or pore defects, forming a composite anodic oxide film with complementary structures. The film thickness in the cross-section is measured using SEM. Figure 3 As shown, the thickness of the barrier oxide layer ranges from 202.7 nm to 212.5 nm, with an average thickness of 208.6 nm. Figure 3 The film thickness values marked in the text are the film thicknesses for the corresponding locations.
[0050] Example 3 The method for preparing the composite anodic oxide film in this embodiment includes the following steps: S1. Pretreatment: The metal substrate sample is 6061 aluminum alloy, and it is subjected to degreasing, water washing, etching, water washing, purification and high-pressure water washing in sequence. S2. First anodizing treatment: The pretreated sample is placed in an electrolyte for the first anodizing. The electrolyte for the first anodizing is a 5% (w / w) oxalic acid solution. The anode temperature is controlled at 20 °C, and a constant current mode is used with a current density of 1 A / dm³. 2 The anode time is determined according to the required film thickness. The anode time is 100 min, which forms a porous oxide layer with a thickness of 20 μm. S3. Second anodizing treatment: The sample obtained from the first anodizing treatment is washed with water, dried, and subjected to a second anodizing. The electrolyte for the second anodizing is a 5% (w / w) ammonium adipate neutral solution. The anode temperature is controlled at 40 ℃, the voltage is 100 V using a voltage stabilization method, and the anodizing time is 45 min to form a dense barrier oxide layer. After washing with water and drying, the drying temperature is 60 ℃ and the drying time is 2 h to obtain a composite anodized film consisting of a barrier oxide layer on the inner side and a porous oxide layer on the outer side. This anodized film has a double-layer composite structure.
[0051] The final oxide film formed in this embodiment is a two-layer composite structure. The bottom layer is a dense, non-porous barrier oxide layer, and the top layer is a porous oxide layer. The two layers are tightly bonded, without delamination or pore defects, forming a composite anodic oxide film with complementary structures. The film thickness in the cross-section is measured using SEM. Figure 4 As shown, the thickness of the barrier oxide layer ranges from 157.6 nm to 163.0 nm, with an average thickness of 160 nm. Figure 4 The film thickness values marked in the text are the film thicknesses for the corresponding locations.
[0052] Comparative Example 1 The method for preparing the anodic oxide film in this comparative example includes the following steps: For pretreatment, the metal substrate sample is 6061 aluminum alloy, which is subjected to degreasing, water washing, etching, water washing, purification and high pressure water washing in sequence. For anodizing, the pretreated sample is placed in an electrolyte solution with a mass concentration of 5% oxalic acid. The anode temperature is controlled at 20 °C, and a constant current mode is used with a current density of 1 A / dm³. 2 The anodic oxidation time is 100 min, depending on the required film thickness. After washing and drying, the drying temperature is 60 ℃ and the drying time is 2 h, resulting in a total thickness of 20 μm for the anodic oxide film.
[0053] This comparative example only underwent one anodizing process, and the preparation process is as follows: Figure 14 As shown, the electrolyte was an oxalic acid solution. SEM cross-sectional observation revealed that the average thickness of the barrier oxide layer in the obtained anodic oxide film was only 54.3 nm, indicating that the majority of the film was porous. Figure 5 As shown, Figure 5 The film thickness values marked in the text are the film thicknesses for the corresponding locations.
[0054] Voltage withstand test, impedance test and corrosion resistance test were performed on the test pieces containing anodic oxide film. The results are shown in Table 1.
[0055] Comparative Example 2 The method for preparing the anodic oxide film in this comparative example includes the following steps: For pretreatment, the metal substrate sample is 6061 aluminum alloy, which is subjected to degreasing, water washing, etching, water washing, purification and high pressure water washing in sequence. For anodizing, the pretreated sample was placed in an electrolyte solution with a mass concentration of 5% ammonium adipate. The temperature was controlled at 40 °C, the voltage was stabilized at 200 V, and the anodizing time was 45 min. The sample was then washed with water and dried at 60 °C for 2 h. The total thickness of the resulting anodized film ranged from 267.3 nm to 322.0 nm.
[0056] This comparative example underwent only one anodizing process, i.e., a single barrier anodizing, such as... Figure 6 As shown, SEM cross-sectional observations reveal that the average total thickness of the anodic oxide film is only 295 nm, meaning the average thickness of the barrier layer is also 295 nm. Figure 6 The film thickness values marked with 'b' are the film thicknesses of the corresponding locations.
[0057] Voltage withstand test, impedance test and corrosion resistance test were performed on the test pieces containing anodic oxide film. The results are shown in Table 1.
[0058] Table 1 Test results of Example 1, Comparative Example 1 and Comparative Example 2
[0059] As shown in Example 1, Comparative Example 1, Comparative Example 2, and Table 1, the oxide film finally formed in Example 1 has a double-layer composite structure. The bottom layer (inner side) is a dense, non-porous barrier layer with an average film thickness of 283 nm, and the upper layer (outer side) is a porous oxide layer of 20 μm. The two layers are tightly bonded, without delamination or pore defects, forming a composite anodic oxide film with complementary structure. The composite anodic oxide film of Example 1 has a withstand voltage of 1078 V, which is 25.93% higher than that of Comparative Example 1; its impedance is 3320 Ω, which is 14.48% higher than that of Comparative Example 2; and the composite anodic oxide film of Example 1 has a corrosion resistance time of 34 min in 3% HCl, which is 78.95% higher than that of Comparative Example 2. The oxide film of Comparative Example 1 has an impedance of only 182.45 Ω, indicating poor resistance to hydrochloric acid corrosion; the oxide film of Comparative Example 2 has a poor withstand voltage of only 17 V.
[0060] Comparative Example 3 The preparation method of the anodic oxide film in this comparative example is basically the same as that in Comparative Example 1, except for the anodizing time and thickness, as detailed in Table 2. The impedance test values are also shown in Table 2. Figure 8 : Table 2 Impedance values corresponding to different oxide film thicknesses
[0061] This comparative example underwent only one anodizing process, as shown in Table 2 and... Figure 8 It is known that increasing the oxidation time by using a single oxalic acid anodic oxidation to increase the thickness of the anodic film cannot improve its impedance performance and corrosion resistance, because the oxide film structure cannot be changed by a single anodic oxidation, and the thickness of the barrier oxide layer cannot be increased.
[0062] Example 4 The method for preparing the composite anodic oxide film in this embodiment includes the following steps: S1. Pretreatment: The metal substrate sample is 6061 aluminum alloy, and it is subjected to degreasing, water washing, etching, water washing, purification and high-pressure water washing in sequence. S2. First anodizing treatment: The pretreated sample is placed in an electrolyte for the first anodizing. The electrolyte for the first anodizing is a 5% (w / w) oxalic acid solution. The anode temperature is controlled at 20 °C, and a constant current mode is used with a current density of 1 A / dm³. 2 The anode time is determined based on the required film thickness; an anode time of 30 min results in a porous oxide layer with a thickness of 1.54 μm. S3. Second anodizing treatment: The sample obtained from the first anodizing treatment is washed with water, dried, and subjected to a second anodizing. The electrolyte for the second anodizing is a 5% (w / w) ammonium adipate neutral solution. The anode temperature is controlled at 40 ℃, the voltage is 200 V using a voltage stabilization method, and the anodizing time is 45 min to form a dense barrier oxide layer. After washing with water and drying, the drying temperature is 60 ℃ and the drying time is 2 h to obtain a composite anodized film consisting of a barrier oxide layer on the inner side and a porous oxide layer on the outer side. This anodized film has a double-layer composite structure.
[0063] Voltage withstand test, impedance test and corrosion resistance test were performed on the anodic oxide film specimen containing the double-layer composite structure. The results are shown in Table 3.
[0064] The final oxide film formed in this embodiment is a two-layer composite structure, such as... Figure 7 As shown, SEM cross-sectional observation clearly distinguishes the following layers: a dense, non-porous barrier oxide layer with a thickness of 297.7 nm at the bottom, and a porous oxide layer with a thickness of 1.54 μm at the top. Figure 7 The film thickness values marked with 'b' are the film thicknesses of the corresponding parts. The two film layers are tightly bonded, without delamination or pore defects, forming a composite anodic oxide film with complementary structure.
[0065] Comparative Example 4 The preparation method of the anodic oxide film in this comparative example is basically the same as that in Comparative Example 1, except that the anodic oxidation time is 30 min and the total thickness of the anodic oxide film obtained is 2 μm.
[0066] Voltage withstand test, impedance test and corrosion resistance test were performed on the test pieces containing anodic oxide film. The results are shown in Table 3.
[0067] Table 3 Test results of Example 4, Comparative Example 2 and Comparative Example 4
[0068] As can be seen from Example 4, Comparative Example 2, Comparative Example 4 and Table 3, the composite anodic oxide film prepared in Example 4 has a very high improvement in voltage resistance, impedance and hydrochloric acid corrosion resistance even with extremely low film thickness. The voltage resistance is 14 to 15 times that of Comparative Example 4 and Comparative Example 2; the impedance is 11.5% higher than that of the oxide film of Comparative Example 2 and 19 times higher than that of the oxide film of Comparative Example 4; and the hydrochloric acid corrosion resistance is 47.4% higher than that of the oxide film of Comparative Example 2 and 2.07 times higher than that of the oxide film of Comparative Example 4.
[0069] Comparative Example 5 The method for preparing the anodic oxide film in this comparative example includes the following steps: For pretreatment, the metal substrate sample is 6061 aluminum alloy, which is subjected to degreasing, water washing, etching, water washing, purification and high pressure water washing in sequence. For the first anodizing treatment, the pretreated sample was placed in an electrolyte solution for the first anodizing. The electrolyte for the first anodizing was a 5% (w / w) oxalic acid solution. The anode temperature was controlled at 15 °C, and a constant current mode was used with a current density of 1 A / dm³. 2 The anode time is determined according to the required film thickness. The anode time is 40 min, resulting in an average thickness of 3.78 μm for the porous oxide layer. The second anodizing treatment involved washing and drying the sample obtained from the first anodizing treatment, followed by a second anodizing process. The electrolyte for the second anodizing was a mixed solution of 2% oxalic acid and 3% boric acid by mass concentration. The anode temperature was controlled at 40 ℃, and a voltage of 80 V was used with a stabilizing method. The anodizing time was 28 min. The sample was then washed and dried at 60 ℃ for 2 h to obtain the anodized film.
[0070] Voltage withstand test, impedance test and corrosion resistance test were performed on the test pieces containing anodic oxide film. The results are shown in Table 4.
[0071] Table 4 shows the test results of voltage withstand capability, impedance, and corrosion resistance for Comparative Example 5.
[0072] In the second anodic oxidation of this comparative example, when the electrolyte is an acidic solution, the oxide film is corroded by the acidic solution during the growth process, forming pores. The oxide film structure is still porous, and the barrier layer cannot continue to grow. Compared with the data of Example 4 in Table 3, the impedance and corrosion resistance are significantly reduced.
[0073] In summary, the preparation method of the composite anodic oxide film of this application adopts two core stages: primary anodic oxidation, acidic electrolyte, porous layer formation, and secondary anodic oxidation, neutral electrolyte, and barrier layer thickening. Through two differentiated anodic oxidation composite formations, a two-layer composite film structure of "dense barrier layer at the bottom + porous protective layer at the top" is constructed, and the thickness of the barrier layer reaches 150 nm to 400 nm, which simultaneously improves the corrosion resistance, voltage resistance, insulation performance and impedance of the oxide film.
[0074] The embodiments described above are merely preferred embodiments of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications, improvements, and substitutions without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a composite anodic oxide film, characterized in that: Includes the following steps: Pretreatment of the metal substrate; The metal substrate is subjected to a first anodic oxidation using an acidic electrolyte to form a porous oxide layer; After the porous oxide layer is formed, a second anodic oxidation is performed using a neutral electrolyte containing ammonium adipate to form a dense barrier oxide layer between the metal substrate and the porous oxide layer, resulting in a composite anodic oxide film consisting of an inner barrier oxide layer and an outer porous oxide layer.
2. The method for preparing the composite anodic oxide film according to claim 1, characterized in that: The thickness of the porous oxide layer formed by the first anodizing is 1 μm to 100 μm.
3. The method for preparing the composite anodic oxide film according to claim 2, characterized in that: The thickness of the barrier oxide layer formed by the second anodizing is 150 nm to 400 nm.
4. The method for preparing the composite anodic oxide film according to claim 3, characterized in that: The current density for the first anodizing step is 0.5 A / dm³. 2 ~2 A / dm 2 The voltage for the second anodizing is 100 V to 500 V. The temperature for the first anodizing is 0 ℃ to 50 ℃; the temperature for the second anodizing is 15 ℃ to 50 ℃. The first anodizing time is 30 min to 200 min; the second anodizing time is 30 min to 60 min.
5. The method for preparing the composite anodic oxide film according to claim 3, characterized in that: The acidic electrolyte includes one or both of oxalic acid and sulfuric acid.
6. The method for preparing the composite anodic oxide film according to claim 5, characterized in that: The oxalic acid has a mass concentration of 1% to 20%; the ammonium adipate has a mass concentration of 1% to 20%.
7. The method for preparing the composite anodic oxide film according to any one of claims 1-6, characterized in that: The pretreatment includes degreasing, water washing, etching, water washing, purification, and high-pressure water washing.
8. A composite anodic oxide film, characterized in that: include, A porous oxide layer located on the surface of a metal substrate; A dense barrier oxide layer located between the metal substrate and the porous oxide layer; The thickness of the barrier oxide layer is 150 nm to 400 nm.
9. An anodic oxide film according to claim 8, characterized in that: The thickness of the porous oxide layer is 1 μm to 100 μm.
10. An application of a composite anodic oxide film, characterized in that: The composite anodic oxide film of claim 8, or the composite anodic oxide film obtained by any one of the preparation methods of claims 1-7, is applied to the preparation of high-end precision metal materials.